2019
DOI: 10.1186/s12862-019-1362-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adult temperature on gene expression in a butterfly: identifying pathways associated with thermal acclimation

Abstract: BackgroundPhenotypic plasticity is a pervasive property of all organisms and considered to be of key importance for dealing with environmental variation. Plastic responses to temperature, which is one of the most important ecological factors, have received much attention over recent decades. A recurrent pattern of temperature-induced adaptive plasticity includes increased heat tolerance after exposure to warmer temperatures and increased cold tolerance after exposure to cooler temperatures. However, the mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 97 publications
(124 reference statements)
0
7
0
Order By: Relevance
“…Plastic responses to environmental change entail a large number of relatively fast physiological mechanisms. In response to thermally challenging conditions, two mechanisms seem to be of particular importance, antioxidant defence mechanisms and the heat shock response (Sørensen et al 2003 ; Zhang et al 2015 ; Franke et al 2019 ). High temperatures generally increase the production of reactive oxygen species (ROS), a by-product of the aerobic metabolism, which act on organic substrates and may induce oxidative damage.…”
Section: Introductionmentioning
confidence: 99%
“…Plastic responses to environmental change entail a large number of relatively fast physiological mechanisms. In response to thermally challenging conditions, two mechanisms seem to be of particular importance, antioxidant defence mechanisms and the heat shock response (Sørensen et al 2003 ; Zhang et al 2015 ; Franke et al 2019 ). High temperatures generally increase the production of reactive oxygen species (ROS), a by-product of the aerobic metabolism, which act on organic substrates and may induce oxidative damage.…”
Section: Introductionmentioning
confidence: 99%
“…Expression patterns of other genes including those involved in metabolism, antioxidant production, transport activity, immune response and transcription also appear to be strongly altered by short-term heat stress (Colinet et al, 2013;Cui et al, 2019;DeBiasse and Kelly, 2016;Franke et al, 2019;Gleason and Burton, 2015;López-Maury et al, 2008;Schoville et al, 2012;Sørensen et al, 2005;Vihervaara et al, 2018). Similar pathways may also be involved in longer-term acclimation under constant temperatures (Metzger and Schulte, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Cold tolerance is a critical environmental factor determining the distribution and population abundance of insects (Fischer & Karl, 2010; Franke et al, 2019; Laiolo & Obeso, 2015; Overgaard & MacMillan, 2017; Plantamp et al, 2019; Stoks et al, 2014). The adaptation and acclimation responses in insects to low temperatures are multifactorial and involve several physiological systems, biochemical adjustments, and a complex combination of changes in gene expression regulation (Laiolo & Obeso, 2015; Liu et al, 2020; Spranghers et al, 2017; Teets et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that the metabolic activity of insects is relatively low when facing cold conditions, their metabolic processes (e.g., energy, lipid, and sugar metabolisms) are still active (Monika et al, 2012). Gene expression studies of many insect species have identified several genes related to cold tolerance (Dunning et al, 2014; Franke et al, 2019; Wang et al, 2014; Zhang et al, 2015). Frost ( Fst ) is a candidate gene associated with the response to hypothermic stress in adult Drosophila melanogaster (Udaka et al, 2013).…”
Section: Introductionmentioning
confidence: 99%